Perkembangan Moral Remaja Akhir dan Implikasinya pada Pendidikan Agama Islam - Trisnawati, Nadia; Rindiani, Natasya; Mortalisa, Tara Putri; Harto, Kasinyo; Pratama, Irja Putra (IAIN Pontianak, 2025)
This study aims to examine the characteristics of late adolescent development and identify its implications for learning, especially in the context of Islamic Religious Education (PAI). Late adolescence is an important transition period towards adulthood marked by significant physical, intellectual, social, emotional, moral, and spiritual changes. To achieve this goal, this study uses a literature study method by reviewing various library sources such as scientific journals, academic books, and relevant articles. The results of the study indicate that late adolescents have complex developmental needs that need to be understood in depth by educators, especially PAI teachers. Understanding these characteristics allows teachers to design learning that is more contextual, holistic, and able to optimally support students' spiritual and moral growth.